Nexus between emotional intelligence and mathematics performance: the role of metacognitive awareness - Bright Asare; Ernest Larbi (Cogent Education)
Purpose The purpose of this study is to examine the moderating and mediating effect of metacognitive awareness on the nexus between emotional intelligence and mathematics performance among undergraduate students.Design/Methodology/Approach The study adopted a descriptive-correlational design utilizing a structured questionnaire, which was designed based on the study constructs (metacognitive awareness, emotional intelligence, and mathematics performance), to collect data from the target population. The data was analyzed using a structural equation modeling (S.E.M.) run from Amos Graphics (v. 23).Findings This study’s findings revealed that metacognitive awareness and emotional intelligence positively influenced mathematics performance. In addition, emotional intelligence positively influences metacognitive awareness. Furthermore, metacognitive awareness positively mediates the nexus between emotional intelligence and mathematical performance. Finally, metacognitive awareness positively moderates the nexus between emotional intelligence and mathematics performance.Originality/Value Most studies have examined the influence of metacognitive awareness and emotional intelligence on mathematics performance among students, but there are inadequate empirical studies that examine the moderating and mediating effect of metacognitive awareness on the nexus between emotional intelligence and mathematics performance.